Corrosion Behavior of the AA2124 Aluminium Alloy Exposed to Ethanol Mixtures (2013)
In the present article was studied the corrosion behavior of the AA2124 aluminum alloy which is a material used to fabricate parts of combustion engines, in a gasoline-bioethanol mixtures with concentrations of 5%, 10% and 20%. The evaluation was performed by potentiodynamics techniques and electrochemical impedance spectroscopy. It was determinate that the corrosion is more evident for mixtures with a greater amount of bioethanol and the corrosion type generated was superficial that begins on a clean surface and extends below it.